2016
DOI: 10.1186/s12909-016-0753-7
|View full text |Cite
|
Sign up to set email alerts
|

Problem-based learning for radiological technologists: a comparison of student attitudes toward plain radiography

Abstract: BackgroundKnowledge and skill expected of healthcare providers continues to increase alongside developments in medicine and healthcare. Problem-based learning (PBL) is therefore increasingly necessary in training courses for radiological technologists. However, it is necessary to evaluate the effects of PBL to completely introduce it in our education programs. As a Hypothesis, it seems that a change occurs in the student’s attitudes by participating in PBL practical training. There is the Semantic Differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Our result revealed that nursing students' attitudes toward patient safety increased significantly after the intervention. In line with our findings, Terashita et al (2016) concluded that plain radiography practical training through PBL promoted students' attitudes toward selfefficacy and increased their self-efficacy through selfcentered learning [41]. Furthermore, Park and Choi's (2015) study showed that PBL plays a considerable role in improving learning attitude, critical thinking disposition, and problem-solving skills in nursing students [42].…”
Section: Discussionsupporting
confidence: 76%
“…Our result revealed that nursing students' attitudes toward patient safety increased significantly after the intervention. In line with our findings, Terashita et al (2016) concluded that plain radiography practical training through PBL promoted students' attitudes toward selfefficacy and increased their self-efficacy through selfcentered learning [41]. Furthermore, Park and Choi's (2015) study showed that PBL plays a considerable role in improving learning attitude, critical thinking disposition, and problem-solving skills in nursing students [42].…”
Section: Discussionsupporting
confidence: 76%
“…AI can empower flipped classroom-like teaching [27,28] and complete the existing bottom-up platforms used to teach radiology [29]. It has been argued that case-based learning should be implemented because it is more effective than traditional top-down approaches and is preferred by radiology educators and students [30,31]. In the hip fracture detection task, the medical students had fundamental knowledge of anatomy, pathology, and the principle of imaging.…”
Section: Discussionmentioning
confidence: 99%
“…New procedures, tools and conceptions are introduced into their curriculum. Nevertheless, technologies overall aim to improve the "cost effectiveness" (Duff et al, 2016, p. 382) of the professions while introducing simulationbased learning even to the aviation known as one of the most artisanal jobs (Kraus & Gramopadhye, 2001), or introducing problem-based and simulated learning in medicine (Baumgart et al, 2017, p. 12;Duff et al, 2016;Morrissey & Heilbrun, 2017;Terashita et al, 2016). We argue that such changes in the education process appear to be another important factor in the changing professional conception we observe.…”
Section: The Polysemic Conception Of Professional Intuitionmentioning
confidence: 99%